2014
DOI: 10.1080/11250003.2014.902124
|View full text |Cite
|
Sign up to set email alerts
|

The amphibianPelophylax bergeri(Günther, 1986) testis poly(ADP-ribose)polymerases: relationship to endocrine disruptors during spermatogenesis

Abstract: In a growing deterioration of the ecosystem both in terms of biodiversity and ecological features, even more problematic is the conservation of species. The aim of this work was to study seasonal variations of biochemical and molecular DNA damage markers in Pelophylax bergeri exposed to potential endocrine disrupting chemicals. Frogs were collected in the main phase of the reproductive cycle: in April and May, during active spermatogenesis and the breeding season, and in October and November, in spermatogeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…In fact, this effect is involved in the regulation of several cellular functions related to the maintenance of genomic integrity (DNA repair, gene amplification, apoptosis) and the expression and propagation of genetic information. Higher expression of PARP in the testis was found, highlighting the role of structural integrity in sperm motility and viability [96].…”
Section: Amphibiamentioning
confidence: 91%
“…In fact, this effect is involved in the regulation of several cellular functions related to the maintenance of genomic integrity (DNA repair, gene amplification, apoptosis) and the expression and propagation of genetic information. Higher expression of PARP in the testis was found, highlighting the role of structural integrity in sperm motility and viability [96].…”
Section: Amphibiamentioning
confidence: 91%
“…Usually, heavy metals can reach the cell nucleus and damage DNA nitrogenous bases because they form reactive oxygen species (ROS) that are highly reactive towards cellular constituents (Piscopo et al, 2018a;Guerriero et al, 2003). Particularly, changes in the levels of ROS can lead to activation or inactivation of transcription factors leading to alterations in the reproductive process (Guerriero et al, 2005;Guerriero et al, 2006;Guerriero 2009;De Maio et al, 2014). Indeed, earlier studies suggested that some heavy metals affect fertility and are associated with abnormal sperm concentration and motility, impaired spermatogenesis, and hormonal imbalance in the exposed organisms (Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A reliable monitoring of contaminated soil or marine remediation requires the species identification [39,44] and their suitable indicators (https://cfpub.epa.gov/si/si_public_record_ report.cfm?dirEntryId=285170, [22]). Ecoremed, the project of remediation of the Land of Fires, adopted an ecofriendly approach in which many bioindicators with the inclusion of the health evaluation of vertebrate biosentinels have been applied.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…Conversely, the use of the DNA repair by PARP activity contributes to explain why the species where numerous also if their DNA testis were seriously damaged. As known, PARP represents the first molecular response to genomic material damage and is correlated to DNA repair [33,39].…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation